2019
DOI: 10.1088/1742-6596/1341/7/072009
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Phenolic Concentration to Antioxidant and Antibacterial Activities of Several Ethanolic extracts from Indonesia

Abstract: Increasing concerns on the adverse effect of synthetic antioxidants and the emergence of antibiotic-resistant Staphylococcus aureus have become two essential problems to be addressed. To tackle them, exploration of natural resources to discover novel antioxidants and/or antibacterial agents is urgently required. The aim of this research was to investigate the correlation of phenolic and flavonoid contents of extracts to their antioxidant and antibacterial activities. Green tea, green coffee, cocoa pod husks, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
3
8
1
Order By: Relevance
“…A summary of extraction yield, TPC, and EGCG content calculated from the obtained GTE are shown in Table 1. (Sartini et al, 2019). In addition, we also found that the GTE prepared in this study contained higher EGCG than our previous result (Sartini et al, 2019).…”
Section: Results and Discussion Extraction Yield Total Phenolic And Egcg Contentssupporting
confidence: 69%
See 3 more Smart Citations
“…A summary of extraction yield, TPC, and EGCG content calculated from the obtained GTE are shown in Table 1. (Sartini et al, 2019). In addition, we also found that the GTE prepared in this study contained higher EGCG than our previous result (Sartini et al, 2019).…”
Section: Results and Discussion Extraction Yield Total Phenolic And Egcg Contentssupporting
confidence: 69%
“…Green tea ethanolic extract, or referred to as green tea extract (GTE), was prepared based on the previously established method (Sartini et al, 2019) with slight modifications. Briefly, GTE was prepared by firstly extracting the coarse powder of green tea by ultrasound-assisted maceration method for 15 minutes using hexane (1:10) to eliminate non-polar compounds.…”
Section: Preparation Of Green Tea Ethanol Extractmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenolic acids, tannins, coumarins, and quinines are among the phenolic compounds commonly extracted from medicinal plants and herbs [ 117 , 118 , 119 ]. Phenolic compounds such as curcumin, carvacrol, and thymol have been shown to inhibit the growth of Candida albicans , the causative agent of candidiasis.…”
Section: Targeting Polymicrobial Diseases: Current and Promising Amentioning
confidence: 99%